Analysis of the communication standardization and industry development of internet of vehicles - Lin LIN; Lu LI; Yuming GE (Dianxin kexue)
The internet of vehicles has become an important strategic direction for the development of the global automobile industry.China accelerates the top-level design,takes the research and deployment of a wireless communication network for vehicles based on C-V2X (now including LTE-V2X and NR-V2X) technology.And it is also required to promote the collaborative deployment of 5G and the internet of vehicles.On the basis of reviewing the latest standardization progress of 3GPP and CCSA in C-V2X,the technical standards problems found in the C-V2X“Four Layers” interoperability application demonstration were refined,and some reference suggestions were proposed for China to improve the C-V2X technical standards.